2014
DOI: 10.1111/bjh.12824
|View full text |Cite
|
Sign up to set email alerts
|

F‐18 FDGPET predicts outcomes for patients receiving total lymphoid irradiation and autologous blood stem‐cell transplantation for relapsed and refractory Hodgkin lymphoma

Abstract: SummaryTotal lymphoid irradiation (TLI) followed by high-dose chemotherapy and autologous haematopoietic stem cell transplant (aHSCT) is an effective strategy for patients with relapsed/refractory classical Hodgkin lymphoma (HL). We report outcomes for patients with relapsed/refractory HL who received TLI followed by high-dose chemotherapy and aHSCT. Pretransplant fludeoxyglucose positron emission tomography (FDG-PET) studies were scored on the 5-point Deauville scale. Of 51 patients treated with TLI and aHSCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 30 publications
0
30
0
3
Order By: Relevance
“…There is extensive literature demonstrating the prognostic significance of CR as measured by functional imaging prior to ASCT, as shown in studies combining both primary refractory and relapsed patients (Jabbour et al, 2007;Castagna et al, 2009;Arai et al, 2010;Mocikova et al, 2011;Smeltzer et al, 2011;Akhtar et al, 2013;Cocorocchio et al, 2013;Nieto et al, 2013;Sucak et al, 2013;Gentzler et al, 2014). Jabbour et al (2007) reported on a retrospective cohort including 66 primary refractory patients, finding a 3-year progressionfree survival (PFS) of 69% for those with negative functional imaging (both PET and gallium scans) compared to 23% with positive scans prior to transplant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is extensive literature demonstrating the prognostic significance of CR as measured by functional imaging prior to ASCT, as shown in studies combining both primary refractory and relapsed patients (Jabbour et al, 2007;Castagna et al, 2009;Arai et al, 2010;Mocikova et al, 2011;Smeltzer et al, 2011;Akhtar et al, 2013;Cocorocchio et al, 2013;Nieto et al, 2013;Sucak et al, 2013;Gentzler et al, 2014). Jabbour et al (2007) reported on a retrospective cohort including 66 primary refractory patients, finding a 3-year progressionfree survival (PFS) of 69% for those with negative functional imaging (both PET and gallium scans) compared to 23% with positive scans prior to transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the clinical characteristics of primary refractory HL is limited, as these patients are often not differentiated from relapsing HL in the medical literature. Ten studies published since 2007 included a total of 372 primary refractory patients (Jabbour et al, 2007;Castagna et al, 2009;Arai et al, 2010;Mocikova et al, 2011;Smeltzer et al, 2011;Akhtar et al, 2013;Cocorocchio et al, 2013;Nieto et al, 2013;Sucak et al, 2013;Gentzler et al, 2014).…”
mentioning
confidence: 99%
“…In particular, the positron emission tomography (PET) status at transplantation, which mirrors the efficacy of the salvage regimen, is fundamental in assessing patients’ prognosis, as progression‐free survival (PFS) rates are significantly better (i.e. more than doubled at 4 and 5 years) in patients who are transplanted with a negative PET scan, compared to those who still display PET positivity (Moskowitz et al , 2010a; Moskowitz et al , 2010b, ; Mocikova et al , ; Smeltzer et al , ; Devillier et al , ; Akhtar et al , ; Gentzler et al , ). Importantly, no differences in outcome have been reported for patients needing 2 salvage regimens instead of only one, provided the pre‐autologous PET scan is negative (Moskowitz et al , ).…”
mentioning
confidence: 99%
“…There is extensive literature demonstrating the prognostic significance of CR as measured by functional imaging prior to ASCT, as shown in studies combining both primary refractory and relapsed patients (Jabbour et al , ; Castagna et al , ; Arai et al , ; Mocikova et al , ; Smeltzer et al , ; Akhtar et al , ; Cocorocchio et al , ; Nieto et al , ; Sucak et al , ; Gentzler et al , ). Jabbour et al () reported on a retrospective cohort including 66 primary refractory patients, finding a 3‐year progression‐free survival (PFS) of 69% for those with negative functional imaging (both PET and gallium scans) compared to 23% with positive scans prior to transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the clinical characteristics of primary refractory HL is limited, as these patients are often not differentiated from relapsing HL in the medical literature. Ten studies published since 2007 included a total of 372 primary refractory patients (Jabbour et al , ; Castagna et al , ; Arai et al , ; Mocikova et al , ; Smeltzer et al , ; Akhtar et al , ; Cocorocchio et al , ; Nieto et al , ; Sucak et al , ; Gentzler et al , ). While first‐line treatment was quite uniform, the majority having received doxorubicin, bleomycin, vinblastine and dacarbazine (ABVD), the salvage and conditioning prior to ASCT differed considerably, and incorporated radiation therapy as well.…”
mentioning
confidence: 99%